Origin of Underwater Oil‐Repellence in Polyelectrolyte Brush Surfaces. Issue 2 (27th September 2020) - Daniel, Dan; Goh, Shermin Simin; Truong, Tran Ngoc Bao; Koh, Xue Qi; Tomczak, Nikodem
Abstract: When submerged under water, polyelectrolyte brush surfaces become highly oil‐repellent. This is due to the ability of the charged moieties on the polymer backbone to retain strong hydration shells. Despite their technological relevance, there is no rational design principle for optimizing the oil‐repellent performance of hydrophilic polyelectrolyte brushes. Using droplet probe atomic force microscopy, the interaction forces between an oil droplet and different polyelectrolyte brushes are measured. It is shown that surfaces are most repellent when there are repulsive electric double‐layer forces that can stabilize a continuous water film beneath the oil droplet. Once a stable hydration layer forms, the oil‐repellent performance is not affected by the polymer brush characteristics, such as its thickness and swelling ratio. Abstract : Characterizing polyelectrolyte brushes using droplet probe atomic force microscopy. It is shown that surfaces are most repellent when there are repulsive electric double‐layer forces that can stabilize a continuous water film beneath the oil droplet.